Adapting Corpus Linguistics for Primary EFL Education in Vietnam: Perspectives from Linguistics Scholars - Le, Thanh Thao; Pham, Trut Thuy (Papanda Publisher, 2023)
This qualitative study investigates the perspectives of Vietnamese linguistics scholars on the integration of corpus linguistics into primary English as a Foreign Language (EFL) education. Through semi-structured interviews with nine scholars from two leading Vietnamese institutions, the research explores the applicability, challenges, and strategies of implementing corpus linguistics for young learners in Vietnam. Participants, categorized into novice, mid-career, and near-end career stages, offer diverse viewpoints on this innovative teaching approach. The underpinning theoretical frameworks are sociocultural theory and constructivist learning theory. The thematic analysis reveals four key themes: tailoring corpus linguistics to young learners’ needs and abilities, the challenges in implementing corpus linguistics in primary EFL settings, the gap between theoretical knowledge and practical application, and the role of cultural context in corpus linguistics application. The study finds a consensus on the need for simplifying and contextualizing corpus materials to suit young learners’ cognitive and cultural backgrounds. Challenges identified include adapting corpus materials, teacher training inadequacies, and curriculum integration difficulties. The gap between theory and practice highlights the need for hands-on teacher training and comprehensive resource development. Furthermore, the importance of culturally relevant corpus materials is emphasized, balancing local and global cultural elements. This study contributes to the field of EFL education by highlighting the specific challenges and strategies for implementing corpus linguistics in the Vietnamese primary education context. It underscores the importance of culturally and pedagogically sensitive approaches in language teaching innovations.